2013
DOI: 10.1038/modpathol.2012.239
|View full text |Cite
|
Sign up to set email alerts
|

Flat pattern of nephrogenic adenoma: previously unrecognized pattern unveiled using PAX2 and PAX8 immunohistochemistry

Abstract: Nephrogenic adenoma is a benign lesion of the urinary tract, particularly the urinary bladder. It is a gross and microscopic mimicker of urothelial neoplasm or metastatic carcinoma. Several histological patterns (tubular, tubulocystic, polypoid, papillary, fibromyxoid) have been recognized, but a flat pattern has not been described. Histologically, nephrogenic adenoma consists of tubules, cysts or papillae lined by flat to polygonal cells with frequent hobnail appearance. The stroma is often edematous or has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 17 publications
(29 reference statements)
0
15
0
Order By: Relevance
“…[ 14 ] In addition, a flat pattern was first described in 2013, and was found in 8 of 15 cases of NA, often mixed with the more traditional tubular, polypoid, and papillary components. [ 15 ] Besides, they also found that flat pattern was a common histomorphological manifestation of NA but could be easily confused with atypical flat urothelial lesions. [ 15 , 16 ] In this case, the histomorphology showed a mixed arrangement of papillary and tubular patterns.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] In addition, a flat pattern was first described in 2013, and was found in 8 of 15 cases of NA, often mixed with the more traditional tubular, polypoid, and papillary components. [ 15 ] Besides, they also found that flat pattern was a common histomorphological manifestation of NA but could be easily confused with atypical flat urothelial lesions. [ 15 , 16 ] In this case, the histomorphology showed a mixed arrangement of papillary and tubular patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguing support for this possibility exists in patients with the rare condition of nephrogenic adenoma, a benign lesion of the bladder or urethra observed most frequently in patients with a history of bladder injury, inflammation, infection, kidney stones, or urogenital surgeries (18,19). Presence of PAX2-and PAX8-immunopositive cells in bladder and urethral biopsies is diagnostic for nephrogenic adenoma (20), but the source of these cells is not completely known. One study demonstrated that exfoliated kidney epithelial cells from donors colonize bladders of kidney transplant recipients who later developed nephrogenic adenoma (18).…”
Section: Discussionmentioning
confidence: 99%
“…[99][100][101][102] Expected Expression in Tumors.-PAX8 is expressed in most types of RCC, including clear cell RCC (80%-98%), papillary RCC (76%-95%), chromophobe RCC (80%-100%), mucinous tubular and spindle cell RCC (100%), clear cell tubulopapillary RCC (100%), sarcomatoid RCC (29%-44%), and metastatic RCC (85%-100%). [99][100][101][102][103][104] Other renal carcinomas also express PAX8, including collecting duct carcinoma (50%-100%) and renal medullary carcinoma (100%) as well as some benign renal neoplasms (eg, oncocytoma, 61%-95%; nephrogenic adenomas, 100%; and mixed epithelial and stromal tumors, 100%). [99][100][101][102][103]105 However, although PAX8 has great sensitivity for renal neoplasms, we and others have seen PAX8 immunoreactivity in a few upper tract urothelial carcinomas (9%-23%), which can be misleading in diagnosing poorly differentiated tumors arising around the renal pelvis.…”
Section: Pax Proteinsmentioning
confidence: 99%
“…[99][100][101][102][103][104] Other renal carcinomas also express PAX8, including collecting duct carcinoma (50%-100%) and renal medullary carcinoma (100%) as well as some benign renal neoplasms (eg, oncocytoma, 61%-95%; nephrogenic adenomas, 100%; and mixed epithelial and stromal tumors, 100%). [99][100][101][102][103]105 However, although PAX8 has great sensitivity for renal neoplasms, we and others have seen PAX8 immunoreactivity in a few upper tract urothelial carcinomas (9%-23%), which can be misleading in diagnosing poorly differentiated tumors arising around the renal pelvis. [99][100][101]106 Most thyroid carcinomas also stain for PAX8, including papillary carcinoma (100%), follicular carcinoma (91%-100%), poorly differentiated carcinoma (75%-100%), undifferentiated carcinoma (50%), anaplastic carcinoma (79%-80%), and medullary carcinoma (41%-75%).…”
Section: Pax Proteinsmentioning
confidence: 99%